THE EFFECT OF INSTITUTIONAL ENVIRONMENT TOWARD ENTREPRENEURIAL MARKETING AND ITS IMPACT ON CULINARY SMEs' PERFORMANCE - Zahara, Zakiyah; Muslimin, Muslimin; N., Cikal Rambasae (Jurnal Aplikasi Manajemen, 2023)
SMEs necessitate effective marketing approaches and strategies to augment their marketing performance. Entrepreneurial marketing functions as an alternative to appropriate marketing management in order to portray the current state of SMEs. The aim of this investigation is to scrutinize the influence of the institutional environment on marketing performance, with entrepreneurial marketing serving as a mediating factor. Scholars executed a descriptive-causal examination, accumulating data from 100 participants who were selected from a pool of 5,830 SMEs in Palu City, Indonesia. The process of data collection was conducted through online and offline methods, employing questionnaires and Google Forms. Subsequently, the gathered data was assessed employing the Smart-PLS software and a structural equation model. The discoveries divulge that all hypotheses, encompassing both direct and indirect impacts, were accepted, apart from the association between the institutional environment and marketing performance, which was refuted. This study emphasizes the pivotal role of the institutional environment in shaping the circumstances of entrepreneurial marketing and amplifying the marketing performance of SMEs.